Learning Paradigm Shift By Era Modern - Sukisno, Sukisno; Nur'aini, Siti; Widiyawati, Rista; Jabbar, Aisyah Abdul (JURNAL PEDAGOGY, 2025)
Education has become an increasing focus of attention in this modern era, especially with the shift in the learning paradigm that accompanies technological developments and changing societal needs. This article explores the transformation in the role of teachers, curriculum innovation according to the development of the education world and needs, the use of technology-based learning media, and identifying challenges such as technology gaps, cultural adaptation, professionalism of educators, and education management are still obstacles in realizing an ideal learning system. Therefore, modern education must continue to develop holistically to create a learning ecosystem that is inclusive, flexible, and relevant to the needs of the times.